“MAKING AND PRESENTING“ ETHNOGRAPHIC FILMS: PRACTICAL AND ETHICAL DILEMMAS IN VISUAL ANTHROPOLOGY - Manca Filak; Žiga Gorišek (EtnoAntropoZum, 2016)
In the following essay the authors discuss visual anthropology based upon their own experiences with ethnographic films. Through the analysis of their work they are thinking about visual representations that are created through the process of making and presenting different visual materials. Both processes include important ethical issues, as well as other problems that we face when using methods of visual anthropology.